Determine the probability distribution function of frosts in Iran during the period (1981-2010) - Mohammad daraei; Peyman Mahmoudi; Behroz sari sarraf; Ali Mohammad khorshiddost (تحقیقات کاربردی علوم جغرافیایی)
Agricultural sector is most dependent on climate, and climate is the main determinant of time, location, production resources, and productivity of agricultural activities. The first event of zero-degree temperature in fall and its last event in spring is important for agriculture. This information is used to determine the species suitable for planting in each area. The present study seeks to identify the probability distribution function for extracting statistical characteristics of frost events in Iran. For this purpose, the history of early autumn and late spring frosts were extracted using daily minimum temperatures of 44 synoptic stations in Iran for a period of 30 years (1981-2010). After fitting various distributions, the best distribution was selected using Anderson-Darling goodness of fit test. Results indicated that most stations follow the Wakeby distribution. Based on the calculations, the first day of frost occurs in the highlands of the Northwest (Saqez, Hamedan, Ardabil, and Zanjan), Northeast (Bojnoord, Torbat-e Heydariyeh, Birjand, and also the Central Zagros Mountains (Shahr-e Kord), due to proximity with cold lands of the North such as Siberia and Northern Europe as well as early entry of westerly winds to this region compared to other regions of Iran will occur. And the latest event of the first day of frost occurs a little farther from the southern coast of Iran in a narrow strip along the coast and parts of the northern coasts (from Babolsar to Bandar Anzali). The earliest event of the last day of frost occurs in the same area in early February. The latest day of frost in Iran occurs in Azerbaijan, Kurdistan, Khorasan, and highlands of the province of Chahar Mahal and Bakhtiari